1468. PCV13 Serotype Trends Over Time in Pneumococcal Community Acquired Pneumonia: Which Method(s) Work Best?. (26th November 2018) - Leblanc, Jason; Elsherif, May; Ye, Lingyun; Mackinnon-Cameron, Donna; Ambrose, Ardith; Hatchette, Todd; Martin, Irene; Andrew, Melissa K; Boivin, Guy; Bowie, William R; Green, Karen; Johnstone, Jennie; et al.
Abstract: Background: Recent studies have shown that a 13-valent pneumococcal conjugate vaccine (PCV13) was effective at preventing vaccine-type pneumococcal community acquired pneumonia (CAPSpn ) in healthy adults. With the anticipated herd immunity from routine infant immunization with PCV13 used since 2010, the benefits of adult immunization in Canada were unclear and surveillance for CAPSpn with serotype distributions was needed. This study aimed to compare PCV13 serotype trends in CAPSpn from 2010 to 2015 using various laboratory methods. Methods: Active surveillance for CAP was performed from 2010 to 2015 in adult hospitals across five Canadian provinces. Bacteremic CAPSpn cases were identified using blood culture, and nonbacteremic CAPSpn cases by sputum culture or using a PCV13-specific urine antigen detection (UADPCV13 ). Serotype was assigned using Quellung reaction, PCR, or UADPCV13 . CAPSpn cases were categorized by laboratory test(s), age, or disease (bacteremic or nonbacteremic CAPSpn ). Results: A diagnostic test for S. pneumonia e was performed on 6, 687 CAP cases. S. pneumoniae positivity decreased from 2011 to 2014, and increased again in 2015. PCV13 serotypes followed a similar trend, where the decline in PCV13 serotypes attributed to serotypes 7F and 19A was noted, and the proportion of serotype 3 increased over time. Similar trends were seen regardless of whether data were categorized by laboratory test(s), age, or disease. Conclusion: Our data suggest that all methods showed similar trends in PCV13 serotype distribution over 2010 to 2015. Herd immunity through childhood immunization with PCV13 was evident, but insufficient to afford complete protection to hospitalized adults. CAPSpn remained a significant cause of morbidity and mortality in hospitalized adult, and serotype 3 seems to be persisting despite herd immunity seen with other serotypes. Ongoing surveillance is required. Disclosures: T. Hatchette, GSK: Grant Investigator, Research grant; Pfizer: Grant Investigator, Research grant; Abbvie: Consultant, Speaker honorarium. M. K. Andrew, GSK: Grant Investigator, Research grant; Pfizer: Grant Investigator, Research grant; Sanofi Pasteur: Grant Investigator, Research grant. A. McGeer, GSK: Grant Investigator, Research grant; Hoffman La Roche: Grant Investigator, Research grant; Sanofi Pasteur: Grant Investigator, Research grant. M. Semret, GSK: Grant Investigator, Research grant; Pfizer: Grant Investigator, Research grant. S. Trottier, CIHR: Grant Investigator, Research grant. S. A. McNeil, GSK: Grant Investigator, Research grant; Pfizer: Grant Investigator, Research grant; Merck: Collaborator and Consultant, Contract clinical trials and Speaker honorarium; Novartis: Collaborator, Contract clinical trials; Sanofi Pasteur: Collaborator, Contract clinical trials.